Use a suitable identity to get each of the following products.

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(vii)

(viii)

(ix)

(x)

(i) Using Identity (a + b)^{2} = a^{2} + 2ab + b^{2}

In the given expression a = x, b = 3

On substituting these values in the above identity, we get

(ii) Using Identity (a + b)^{2} = a^{2} + 2ab + b^{2}

In the given expression a = 2y, b = 5

On substituting these values in the above identity, we get

(iii) Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2}

In the given expression a = 2a, b = 7

On substituting these values in the above identity, we get

(iv) Using Identity (a - b)^{2} = a^{2} - 2ab + b^{2}

In the given expression a = 3a, b = 1/2

On substituting these values in the above identity, we get

(v) Using Identity (a + b)(a - b) = a^{2} - b^{2}

In the given expression a = 1.1m, b = 0.4

On substituting these values in the above identity, we get

(vi) Using Identity (a + b)(a - b) = a^{2} - b^{2}

In the given expression a = b^{2}, b = a^{2}

On substituting these values in the above identity, we get

(vii) Using Identity (a + b)(a - b) = a^{2} - b^{2}

In the given expression a = 6x, b = 7

On substituting these values in the above identity, we get

(viii)Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2}

On substituting these values in the above identity, we get

(ix) Using Identity (a + b) ^{2} = a^{2} + 2ab + b^{2}

In the given expression a =

On substituting these values in the above identity, we get

(x) Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2}

In the given expression a =

On substituting these values in the above identity, we get

4